Improving Pronunciation Ability by Using Animated Films - Titik Lina Widyaningsih (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2018)
The main purpose of this research was to improve the students’ pronunciation ability by using AnimatedFilms. The subject of this research were the students of first semester of English Department of STKIP PGRI Tulungagung in the academic year of 2016/2017. This research used Classroom Action Research Method. The research was conducted in two cycles from Octoberuntil Decemberat the first semester students of English Department of STKIP PGRI Tulungagung.The research data were collected by using techniques of observation,interview, and test (pre-test and post-test). The research findings prove that Animated Films could improve the first semester students’ pronunciation ability. The result of the research implies that English teachers need to choose the appropriate media in teaching pronunciation. The appropriate media to teach pronunciation is animated films